UNSUR PERBUATAN MELAWAN HUKUM YANG DILAKUKAN OLEH NOTARIS DALAM PEMBUATAN AKTA - BOYSAL PARULIAN SIHOMBING (PREMISE LAW JURNAL, 2016)
Illegal act done by a Notary in writing a deed is contrary to legal norms an, therefore, it is against law which regulates a Notary’s authority, obligation, and prohibition in writing a deed according to Article 84 and Article 85 of UUJN. The offences are illegal act, victim that suffers a loss, violation against law, and causal relation between loss and wrong doing. A Notary’s liability for what he has done is the consequence and punishment upon him. He will be liable for civil case, criminal case, position, code of ethics, and State’s administration. His letter of appointment issued by the Minister of Law and Human Rights can be revoked and can be dismissed. The effort to prevent from illegal act by a Notary is the supervision and fostering by the Minister on a Notary by establishing Notarial Supervisory Council and supervision and fostering by Notarial association, INI (Indonesian Notarial Association) by establishing Review Board. Keywords: Illegal Act, Notary, Notarial Deed